Windows Phone 7 made simple - Westfall, Jon (Apress, 2011)
Looks at the features and functions of the Windows Phone 7 series, covering such topics as making phone calls, using email, setting up and using Facebook and Twitter, security, browsing the Web with Internet Explorer, using Microsoft Office mobile, and connecting to Zune software